KONDISI LINGKUNGAN, PERILAKU HIDUP SEHAT, DAN STATUS KESEHATAN KELUARGA WANITA PEMETIK TEH - Yuli Fitriyani; Katrin Roosita; Yekti Hartati Effendi (Food and Nutrition Society of Indonesia, 2008)
The aim of this research is to study environmental condition, healthy life behaviour, and health status of women tea picker’s family in PTPN VIII Pengalengan, Bandung, West Java. The cross sectional study design is used in this research and total number of samples are 92 family of women tea picker who live in Malabar Plantation. The inclusion criteria of the sample is having children 0-72 month age and willing to be interviewed. The place of the research was chosen purposively. Malabar Plantation was chosen from the other five plantations (clusters) because of its easier access and the homogenous characteristics of inter cluster. Primary data consists of family characteristics, environmental condition, healthy life behavior, and family’s health status. Secondary data consists of general description of Malabar Plantation and Banjarsari Village. Data was processed and analyzed with descriptive statistic and inference, and correlation analysis used Rank Spearman correlation test. The results revealed that the family were live in average (moderate) environmental condition, and only a few families live in good environmental condition. Their family’s health behaviour was good. The symptoms/kind of diseases which found among the samples were fever, acute respiratory infection (ARI) diseases, digestion organ diseases, skin disease, and hepatitis. Family’s member who was the most susceptible to disease was children. The related factors to environmental condition of women tea picker’s family were family income and family size. The water source used by the families, which was one of factors of the environmental condition’s, was related to health status of women tea picker’s family. The acute respiratory infection (ARI) disease and hepatitis cases in family were related to better water source for taking a bath, wash the dishes and wash hands after defecation. Better water source, then less cases of the diseases.